PENGARUH JUMLAH ALTERNATIF JAWABAN TES OBYEKTIF BENTUK PILIHAN GANDA TERHADAP RELIABILITAS,TINGKAT KESUKARAN DAN DAYA PEMBEDA - Idrus Alwi (LPPM, 2010)
The purpose of this research was to examine the effect of the alternative numbers in a multiple choice test on reliability, level of difficulty and discriminatory power. The random technique was implemented to take the sample which consisted of the third year students of MTs N 7 Jakarta. The sample was 150 student. The data were collected through achievement test of mathematics. The one way analisys of variance was used to analyze the data. The result indicated that : (1) the alternative number in a multiple choice test had a significant effect on reliability of the test, (2) The alternative number in a multiple choice test had no significant effect on the level of difficulty, (3) but the alternative number in a multiple choice test had a significant effect on the discriminatory power. Keywords: alternative numbers, multiple choice, reliability